2008
DOI: 10.1159/000114250
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Metabolic Syndrome and Uterine Leiomyomas: A Case-Control Study

Abstract: Background/Aims: Uterine leiomyomas are the most common gynecological benign tumor and greatly affect reproductive health and well-being. The pathophysiology and epidemiology of fibroids are poorly understood. Obesity and elevated blood pressure have been reported to be predisposing factors. In this study, we investigated whether fibroids are associated with some criteria of the metabolic syndrome. Methods: The case patients were 213 women who underwent hysterectomy or myomectomy for fibroids, and the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 20 publications
7
60
2
1
Order By: Relevance
“…2,4,5,[14][15][16][17] Although high BMI has previously associated with fibroid risk, we did not observe a strong association with BMI, although there was evidence that increasing BMI is associated with increasing risk (overweight OR = 1.68; obese OR = 1.56). [18][19][20] However, the associations between BMI and fibroids have been inconsistent in prior published literature.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5,[14][15][16][17] Although high BMI has previously associated with fibroid risk, we did not observe a strong association with BMI, although there was evidence that increasing BMI is associated with increasing risk (overweight OR = 1.68; obese OR = 1.56). [18][19][20] However, the associations between BMI and fibroids have been inconsistent in prior published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between reproductive factors and LMA is very complex and may be altered by factors such as parity or other anthropometric characteristics (Takeda, 2008) their interaction with AhR levels is not identified yet.…”
Section: Role Of Endocrine Disrupting Chemicals In Thementioning
confidence: 99%
“…1 The authors suggest that of BMI is not a main factor in obesity whereas increases of distribution of body fat, waist circumference and waisthip ratio may be associated with certain diseases including myoma uteri. 9 Unlike these studies, in the study of Takeda et al, 19 BMI was found significantly higher in the patient group and obesity was reported as a risk factor for myoma uteri formation. In this study, the waist circumference was ignored because although waist circumference is diagnostic on abdominal obesity, it is reported that, visceral fat rate could not be measured by waist circumference on patients with myoma uteri due to enlarged uterus volume.…”
Section: Discussionmentioning
confidence: 81%
“…In these studies, no significant correlation was found between fasting blood glucose level and myoma formation. 1,19 In one of these studies, the idea of "hyperglycemia may increase likelihood of myoma uteri formation" was inferred, because of fasting plasma glucose levels were found higher in the patient group. 1 No studies were found in literature which investigates the effect of HbA1c on myoma uteri formation.…”
Section: Discussionmentioning
confidence: 99%